PANEN RAYA KELAS SEJARAH: AN EXHIBITION-BASED DIFFERENTIATED HISTORY CLASSROOM TO ENHANCE 21ST CENTURY 4C SKILLS - Wilis, Roro; Kumalasari, Dyah (JURNAL EDUSCIENCE, 2025)
Purpose—This research aims to explore the implementation of the exhibition-based differentiated classroom "Panen Raya Kelas Sejarah" and analyze its implications for developing the 4C skills needed in 21st-century education.Methodology – This research uses a qualitative method with a case study approach at State High School 9 Yogyakarta. Data collection techniques were conducted comprehensively through interviews, observation, and document analysis. The sampling technique was purposive and included several subjects, such as the Vice Principal for Curriculum, Facilities, history teachers, and representatives of students from classes XI and XII of State High School 9 Yogyakarta. Data validity and validity were obtained through data triangulation techniques and analyzed using an interactive model.Findings—The research findings show that the "Panen Raya History Class" has represented a differentiated class that accommodates almost all learners' learning styles. In this context, support from school policymakers has a vital contribution, especially information on learners' psychological tests, time management for the implementation of independent classes, and provision of infrastructure. The successful implementation of the "Panen Raya Kelas Sejarah" has positive implications for improving the 4C skills of the 21st century, including critical thinking, creativity, innovation, communication, and collaboration.Significance – The results of the study are helpful as a reference for history teachers in the context of developing differentiated learning and increasing the ability of the 4Cs of the 21st century, as well as a portrait of the support of school policymakers to improve the quality of learning. Keywords : Differentiated, History Learning, Exhibition, 4C Skills